Utilizing Instagram as Social Media Marketing on the @bssexhaustofficial Account - Hafidz, Akbar Zaelani; Fikri, M. Andi (Procedia of Social Sciences and Humanities, 2024)
Marketing activities that utilize digital media or the internet are often referred to as digital marketing. One of the strategies of digital marketing is to utilize social media as a marketing medium, commonly referred to as social media marketing. One of the social media platforms used as a means of promotion and communication between companies and their consumers is Instagram. Through this research, the researcher aims to examine how Instagram is utilized as social media marketing on the account @bssexhaustofficial. This study aims to understand the application of the AISAS theory (Attention, Interest, Search, Action, and Share) in leveraging Instagram as social media marketing on the account @bssexhaustofficial. The method used in this research is qualitative descriptive research. The results of the research above indicate that the BSS Exhaust Official store utilizes various Instagram features to market its products through a soft selling concept, enhancing audience understanding of the products and building interaction with the audience.